Peran Kepolisian Dalam Pencegahan Tindak Pidana Pembunuhan Disertai Pemerkosaan (Studi Kasus Polsek Labuhan Ruku Kec. Talawi : Kabupaten Batubara, Sumatera Utara) - Muhammad Khotomi Tarigan; Abdul Lawali Hasibuan; Rizkan Zulyadi (Universitas Medan Area, 2020)
Article 16 of the Republic of Indonesia Law No. 2 of 2002 concerning the Indonesian National Police, is a State tool that plays a role in maintaining public order and security, in the context of maintaining domestic security. This type of research in this thesis is empirical juridical and library research methods and field research that is by conducting direct research into spaciousness. In this case the researchers directly conducted research into the Labuhan Ruku Sector Police (POLSEK), Talawi District, Batubara District, North Sumatra. The research results obtained are the crime of murder can occur due to factors that support the occurrence of the act of murder that can be caused through many things including through, conditions, circumstances and so forth that provide space for the occurrence of these things. The role of the police investigator is to uncover the occurrence of a criminal act of murder through a series of acts of search and examination of matters relating to the murder case. Obstacles faced by investigators in uncovering murder cases include, the lack of equipment and facilities and also the absence of witnesses that complicate the examination process.